2005
DOI: 10.1021/ci049652n
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Programming for the Induction of Decision Trees to Model Ecotoxicity Data

Abstract: Automatic induction of decision trees and production rules from data to develop structure-activity models for toxicity prediction has recently received much attention, and the majority of methodologies reported in the literature are based upon recursive partitioning employing greedy searches to choose the best splitting attribute and value at each node. These approaches can be successful; however, the greedy search will necessarily miss regions of the search space. Recent literature has demonstrated the applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Genetic programming is a member of the broad class of evolutionary algorithms that can efficiently search very large parameter spaces for locally optimal solutions to high dimensional materials spaces (Le and Winkler, 2016). The application of evolutionary algorithms for discovery and optimization of materials has been reviewed very recently (Le and Winkler, 2016 be successfully applied to modelling of ecotoxicity data (Buontempo et al, 2005). As the details of the technique can be found in literature (Wang et al, 2006, Buontempo et al, 2005, only a basic overview of the method is provided here.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic programming is a member of the broad class of evolutionary algorithms that can efficiently search very large parameter spaces for locally optimal solutions to high dimensional materials spaces (Le and Winkler, 2016). The application of evolutionary algorithms for discovery and optimization of materials has been reviewed very recently (Le and Winkler, 2016 be successfully applied to modelling of ecotoxicity data (Buontempo et al, 2005). As the details of the technique can be found in literature (Wang et al, 2006, Buontempo et al, 2005, only a basic overview of the method is provided here.…”
Section: Methodsmentioning
confidence: 99%
“…The application of evolutionary algorithms for discovery and optimization of materials has been reviewed very recently (Le and Winkler, 2016 be successfully applied to modelling of ecotoxicity data (Buontempo et al, 2005). As the details of the technique can be found in literature (Wang et al, 2006, Buontempo et al, 2005, only a basic overview of the method is provided here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…the physicochemical descriptors that contribute to the observed toxicity) and to remove the descriptors that are not related to the endpoint of interest. In a previous study, (Buontempo, et al, 2005) demonstrated the use of a genetic programming-based decision tree generation technique for in silico toxicity prediction. They developed a decision tree model, involving five descriptors selected from a pool of more than a thousand descriptors, that has good predictive performance for both training and test datasets.…”
Section: Decision Trees (Dts) Automatic Generation Of Decision Treesmentioning
confidence: 99%
“…An insight into the potential benefits of using optimization‐based prediction models for the toxicity of real‐valued data is provided in Buontempo, Wang, Mwense, and Horan (). In this case, GP is used in the induction of decision trees for application to two eco‐toxicity datasets of organic compounds, both with a large number of inputs and four classes obtained from equal frequency splitting of the endpoint.…”
Section: Related Workmentioning
confidence: 99%